Épocas de consórcio de alho com cenoura em três sistemas de manejo de plantas daninhas em Jaboticabal-SP - Mueller, S. (2001)
This work was carried out using intercropped cultivation of garlic (Allium sativum) and carrot (Daucus carota) in Jaboticabal, SP - Brazil. Four seeding timings for carrot (0, 15, 30 and 45 days after garlic planting) and three weed management systems (herbicide, frequent manual weed control and no weed control) were tested. The effects of this intercropped system on weed control, efficient land use and productivity were determined. The experimental design was a completely randomized block with split-plots and four replications, with carrot seeding timings being the plots and the weed management systems, the sub-plots. The herbicide oxadiazon at 750 g ha-1 did not cause toxicity in the garlic, nor in the carrot plants. Regandress of the timing for the intercropping establishment the Land Equivalent Ratio (LER) values were greater than one. Garlic-carrot intercropping profitability was greater than that of monocultures of garlic crop, mainly under weed management systems, using the herbicide oxadiazon and frequent manual weeding.